Analisis Pemberdayaan Masyarakat Melalui Program Pemanfaatan Serat Olahan Daun Nanas Subang (Pesona Subang) - Andhar Lutfi; Wazirul Luthfi; Ratnasari Putri Utami; Ashlihul Hayati; Diaz Alvin Firdausa; Annisa Nur Fadhlillah (Syntax Corporation Indonesia, 2023)
Social responsibility is an important issue in the corporate context. Moreover, companies operating in the natural resource exploration and mining (extractive) sectors have an obligation to carry out social responsibility as an effort to develop and guarantee the rights of local people and communities around the company area. One of them is the social responsibility carried out by PT Pertamina EP Regional 2 Zone 7 Subang Field which focuses on efforts to manage pineapple leaf waste into natural fiber which has high economic value through the implementation of the Subang Pineapple Leaf Processed Fiber Utilization Program (Pesona Subang). This study aims to examine the implementation of the Pesona Subang Program from a community empowerment perspective starting from planning, implementation, and ultimately generating impacts and benefits for the community, especially the community of Cikadu Village, Cijambe District, Subang Regency. This research uses descriptive qualitative methods through literature sources and all forms of documentation and reporting publications related to the program. Program Pesona Subang provides benefits and positive impacts not only for dealing with the problem of pineapple leaf waste into natural fiber with high selling value, but also strives for the sustainability of the program which is supported by innovation in production management and adequate infrastructure for community productivity. Apart from that, participation from beneficiary communities and local communities is also the main key in the success of achieving this program, so that people are independently motivated.